Effect of the tryptone concentration on the calcium carbonate biomineralization mediated by Bacillus cereus (2018)
Five tryptone concentrations (0.2%, 0.4%, 0.6%, 0.8% and 1.0%) were evaluated on calcium carbonate biomineralization processes, using 0.5% of calcium acetate. A culture of Bacillus cereus, isolated from the gardens of The Universidad Pontificia Bolivariana (Medellin, Antioquia, Colombia) was used in all the assays. The experiments were monitored by pH measurements and mineralogical analyses of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Scanning electronic microscopy (SEM). Vaterite was the predominant polymorph in the precipitates after 6 days of the process. However, a considerable proportion of calcite appeared (above 30%) when the tryptone concentration was 0.4% or below. Additionally, the other experiments had a similar precipitate formation (between 3.2-3.6 g/L) except the assay using 0.2% of tryptone, which presented a low calcium carbonate production (1.79 g/L). A tryptone concentration below 0.4% would limit the bacterial metabolism and CO2 formation, necessary for calcium carbonate production.